Keanekaragaman jenis tumbuhan invasif di Kawasan Hutan Sillu Kabupaten Kupang - Aleng, Helena Yuni Rizky; Kleruk, Flora Evalina Ina; Almulqu, Aah Ahmad (Trend and Future of Agribusiness, 2024)
Background: Invasive plants are plants that grow and spread to areas outside their original habitat. Invasive plants invade many forest areas, tourist attractions, and vegetation in Indonesia. Invasive plants can affect the composition of native vegetation so that it can threaten biodiversity in an area. The purpose of this study was to determine the diversity of invasive plant species in the Sillu Forest Area, Kupang Regency. Methods: The research method used is systematic sampling method with the placement of measuring plots is a plot line. Findings: The area studied was 70.24 Ha with the sampling intensity used was 5% and the number of measuring plots was 88 measuring plots. The vegetation analysis carried out was Density, Relative Density, Frequency, Relative Frequency, Important Value Index (INP) and Species Diversity Index. Conclusion: The results showed that there were 8 species from 5 families of invasive plants in the study site, namely krinyuh (Chromolaena odorata (L.) R.King & H. Rob), Ayam's Tahi Flower (L.). Rob, Bunga Tahi Ayam (Lantana camara L), Grinting grass (Cynodon dactylon), Jariji grass (Digitaria sanguinalis), Teki grass (Cyperus rotundus), Gala-gala (Amorpha fruticosa L), Ipomoea (Ipomoea indica (Burm.Merr) and Putri malu (Mimosa pundica L). The highest Index of Important Value is the type of Krinyuh (Chromolaena odorata (L.) R.King & H.Rob which is 62% while the lowest Index of Important Value is the type of Putri malu (Mimosa pundica L) which is 2%. The value of Diversity Index of invasive plants with 0.7683, which is included in the low diversity category.